PENERAPAN PEMBELAJARAN ACCELERATED LEARNING DENGAN MEDIA PIKTOGRAM UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI KELAS VII SMP NEGERI 1 BANGSALSARI TAHUN AJARAN 2008/2009 - Rohman, Minahur (Pendidikan Biologi,Universitas Islam Jember, 2012)
Problem in Indonesia especially in education side cause low of Indonesian quality. Based on data which gave by one of international committee from PBB, United Nations Development Programme (UNDP) rating of Human Development Index (HDI) Indonesia in position 111 in world. From the explanation above so need to an research about applying of accelerated learning with pictograph media for increasing biology learning product. Based on research gotten conclusion that accelerated learning with pictograph media able to increasing student learning product with average value 80,14, percentage classical comprehensiveness 92,86%, and able to increase student activity with percentage 91,43% (in rank really good).Key word: accelerated learning, learning product, student activity